People Andwork in Events and Conventions: A Research Perspective - Baum, Thomas (CABI, 2014)
Events, as Mair rightly points out in Chapter 1 of this book, are no new phenomenon. Events, whether ceremonial, religious or sporting, have featured in all organized societies from earliest recorded time and continue to be an important dimension of contemporary living at a local, national and global scale. Clearly, alongside ancient events was to be found a level of organization and a requirement for workers to support such events, in their development and set up, delivery and post-event dismantlement. What is unclear is the status of those engaged in event organization in terms of their demographics, relationship to those leading the event, whether political or religious, or indeed whether they were free citizens or enslaved labour. Discussion of such ancient events in the literature today does not give us much indication of their organization or who the event workers were, although we may surmise answers to some of these quandaries – their frequent religious or political context means that the primary source for organization would have been within the respective religious or political elites or, indeed, both groups. Slave labour was commonplace in ancient societies, such as those in Egypt, Greece and Rome, so it is reasonable to assume a significant role for this class of workers at major events. Notwithstanding many evident differences between events in the ancient world and those with which we are familiar today, the nature of organization and work is likely to have included many tasks with which contemporary event organizers will be familiar